ASM and the UN SDG Publishers Compact: year one - Lorraine F. Clark; Amanda Donaldson; Michael E. Lerman (mSphere)
ABSTRACT The United Nations (UN) Sustainable Development Goals (SDG) represent an important set of global priorities, addressing the most urgent environmental, economic, and social challenges facing humankind. The American Society for Microbiology (ASM) signed the UN SDG Publishers Compact in March 2024, to lend its voice to this vital initiative, as indeed not only do the SDGs align with ASM’s mission but microbes themselves can play significant roles in, for example, sustainable agriculture, clean energy, and human health. In its first year as a signatory, ASM has pursued, published, and highlighted sustainability-focused work in its journals, has raised awareness through internal efforts and joint efforts with other scientific organizations, and has prioritized the SDGs in its conferences and other programs. We commemorate our achievements in this first year and look forward to future initiatives, innovations, and collaborations toward a sustainable future.